Predicting Perceived Problems in 24-hour Dietary Recall, and Evaluating its Potential for Behaviour Change: A Quantitative Think-Aloud Approach in an Australian Population - Mackenzie, Katlyn Marie (Curtin University, 2023)
This thesis incorporates the think-aloud methodology across two studies that investigate the experience of 24-hour dietary recall and its potential for improving future nutritional behaviours. The methodological integration incorporated in the thesis aids in revealing different aspects of thinking when recalling and assessing our dietary behaviours, as well as their importance in the accuracy of self-reported psychological and nutritional research.